Surfactin suppresses postharvest gray mold in Actinidia arguta fruit via direct antifungal activity and induced host resistance - Feiyang Wang; Sen Dong; Hang Che; Baodong Wei; Dazhi Zhang; Bingxue Li; He Gao; Shunchang Cheng (Food Control, 2027)

Simulating the PM2.5 in southern Taiwan under high-pressure return flow during the Kao-Ping Experiment (KPEx) - Ming-Tung Chuang; Charles C.K. Chou; Chuan-Yao Lin; Wei-Che Lin; Neng-Huei Lin; Wei-Nai Chen; Steven Soon-Kai Kong (Atmospheric Research, 2027)

Alkalinity stress disrupts the liver–gut axis and induces hyperammonaemia in common carp: uridine mitigates toxicity through nitrogen metabolic reprogramming - Xinghua Che; Yongquan Zhang; Longwu Geng; Meiqi Xing; Xiaodan Shi; Shijie Zhang; Wei Xu; Xinchi Shang (Aquaculture, 2027)

Thermal kinetics of biochar-ethylene vinyl acetate for waste-to-energy: Particle swarm optimization, cloud computing, and artificial intelligence - Wei-Hsin Chen; Che-An Lin; Partha Pratim Biswas; Chih-Chun Chen; Biqing Liang; Sheng-Lun Lin; Hwai Chyuan Ong; Aristotle T. Ubando (Fuel, 2026)

Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

A potent protein vaccines OmpW induces strong protective immunity against Klebsiella pneumoniae in a mouse model - Ting Huang; Siyou Che; Hong Zhang; Wei Jiang; Danrui Hao; Zheng Lv; Yang Yuan; Yundong Zhang; Ruibin Yang; Linqiu Luo; Lufeng Dan; Yiwen Chu; et al. (Medical Microbiology and Immunology, 2026)

Devonian Jinshuikou pegmatites at the northern margin of the Tibetan Plateau: UPb and SmNd constraints on their genetic relationship with regional granitoids - Si-Qi Liu; Shao-Yong Jiang; Mostafa Fayek; Hui-Min Su; Yu-Ying Che; Wei Wang; Qinglin Xia (Lithos, 2026)

A corn Stalk-Derived carboxymethyl cellulose for efficient Molybdenite-Talc flotation separation by weakening hydrophobic attraction - Qing Sun; Wei Chen; Yuhang Che; Siyan Zou; Jie Zhou; Kai Zeng; Yangge Zhu (Minerals Engineering, 2026)

Engineering Co-N4 active sites in heptazine-porphyrin organic polymer to boost non-radical singlet oxygen generation in peroxymonosulfate activation - Xiang Li; Yu Tian; Yalong Xu; Bo Liu; Shi Zhou; Wei Jiang; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Alternariol, a mycotoxin, induces oxidative stress, inflammation, and apoptosis in human astrocytes: Protective effects of eicosapentaenoic acid - Che-Sheng Chu; Wei-Chih Sun; Wei-Zhe Liang (Food and Chemical Toxicology, 2026)

Water-retention performance of vegetation-polymer improved soils under extreme drought conditions - Jin Liu; Ke Ma; Wei Wu; Mengya Sun; Meng Wu; Wenyue Che; Xingping Shi; Zezhuo Song (Engineering Geology, 2026)

Upcycling of waste polycarbonate into polyallyls for degradable high-performance BMI/polyallyl-based thermosets/CFRPs - Che-Wei Lin; Lu-Ling Chen; Dula Daksa Ejeta; Ching-Hsuan Lin (Chemical Engineering Journal, 2026)

Redefining the control volume of PFAS thermal treatment: Achieving systemic net reduction via closed-loop GASMILD combustion - Wei Tang; Yi-Che Hsiao; Sheng-Lun Lin; Jhong-Lin Wu; Chien-Er Huang (Chemical Engineering Journal, 2026)

Synergistic bulk–interfacial regulation for wide-temperature aqueous zinc batteries - Yuanhang Wang; Hui Zhi; Yiming Zhang; Chenglin Miao; Yicheng Tan; Junzhi Li; Jiacheng Zhou; Che Yuan; Mengjie Lu; Wei Han (Chemical Engineering Journal, 2026)

Metagenomics indicates new taxa in Candidatus Saccharimonadia and proposal of Parviradicicola hetaonensis gen. nov. sp. nov. and Parviputeicola dengkouensis gen. nov. sp. nov. following the rules of the SeqCode - Yanxing Wang; Lijia Ye; Chunling Cao; Gen Che; Chengzhi Zhang; Qiuqin Wei; Yu Hong; Kai Jiang (Systematic and Applied Microbiology, 2026)

A distinct electrochemical mechanism governing chalcopyrite flotation in hematite-rich IOCG ores - Wei Che; Richard Lee; Yongjun Peng (Minerals Engineering, 2026)

Non-contact discharge estimation using physics-informed neural networks and CNN-enhanced image velocimetry - Yen-Cheng Lin; Cheng-Wei Wu; Hao-Che Ho (Journal of Hydrology, 2026)

CarbonTimer: Overcoming data scarcity in carbon price forecasting with a large time series model - Meiqin Jiang; Jinxing Che; Yaoxin Tan; Wei Dong (Journal of Cleaner Production, 2026)

Energy-efficient dynamic control of carbon capture for hot blast stoves: A physics-constrained and surrogate-based framework - Sihong Cheng; Zichang Che; Wenbo Zhang; Yi Xing; Wei Su; Tao Yue (Fuel, 2026)

Isolation and functional characterization of goose-derived lactic acid bacteria with growth-promoting and gut health benefits in Sanhua geese - Changsheng Jiang; Wenli Shi; Ji Chen; Weitao Wang; Dandan Fang; Wanji Zhan; Wei Zuo; Chuanyan Che; Ahmed H. Ghonaim; Mengmeng Jin; Qianqian Hu; Keli Yang; et al. (Food Chemistry, 2026)

Modal coupling and vibration-based identification of individual tensions in interlinked parallel stay cables - Wen-Hwa Wu; Chien-Chou Chen; Che-Wei Chang (Engineering Structures, 2026)

Amorphous CO2-philic molecular networks via covalent coupling for high-performance TFC hollow fiber membranes - Meta Mamo Goro; Zelalem Gudeta Abdi; Qing-Yun Chou; Ching-Han Chou; Che-Wei Chang; Tai-Shung Chung (Chemical Engineering Journal, 2026)

Quantifying the effects of near-fault fling-step ground motions on seismic performance of offshore wind turbines - Wei Che; Guowei Qin; Yajun Li; Chao Long (Ocean Engineering, 2026)

A dual-stream LSTM–XGBoost framework for mine water inflow forecasting: a case study of the Longfeng coal mine - Wang Hao; Li Bo; Zeng Yi Fan; Liu Pu; Chen Wei; Wang Ze Hui; Che Lu Lu (Journal of Hydrology, 2026)

Microplastic sources and distribution in tropical mangroves: Natural and planted systems in China - Siriporn Pradit; Pei Sun Loh; Preyanuch Jitkaew; Prakrit Noppradit; Thongchai Nitiratsuwan; Thi Phuong Quynh Le; Chantha Oeurng; Ty Sok; Che Abd Rahim Mohamed; Choon Weng Lee; Chui Wei Bong; Gusti Z. Anshari; et al. (Estuarine, Coastal and Shelf Science, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Thermal dynamics of an intermittent subtropical stream controlled by surface water-groundwater interactions: evidence from distributed temperature sensing and heat-budget modeling - Yen-Wei Pan; Yu-Cheng Chen; Tsung-Yu Lee; Yung-Chia Chiu; Shao-Yu Hsu; Che-Ming Chen (Environmental Monitoring and Assessment, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Design and enhancement of bifunctional g-C3N4/Co-UiO-66-NH2 nanocatalyst for photocatalytic degradation in real samples and electrocatalytic energy conversion applications - Yazhini Priya Subbarayalu; Kasimayan Uma; Nagapandiselvi Perumal; Sathiya Balashanmuga Nehru; Mangalaraja Ramalinga Viswanathan; Che-Wei Chang; Lung-Chien Chen; Zong-Liang Tseng (Journal of Water Process Engineering, 2026)

Multimodal detection of microplastics in human kidney stones and multi-omics exploration of renal cell metaflammation - Qingli Zeng; Jinhui Tang; Leilei Zhan; Ruiyin Liang; Chuanli Yang; Ruibin Cai; Jieyu Luo; Jia Xu; Tao Liu; Hongyan Wei; Lin Che (Journal of Hazardous Materials, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

The state of knowledge for engineering with nature: Vegetation as wave buffer - Xifen Chen; Zhan Hu; Tori Tomiczek; Che-Wei Chang; Dan Cox; Maria Maza; Nobuhito Mori; Siddharth Narayan; Sungwon Shin; Tomohiro Suzuki (Coastal Engineering, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

A giant two-stage landslide at Matai'an, Taiwan: insights from seismic source inversion and remote-sensing analysis - Wei-An Chao; Che-Ming Yang (Landslides, 2026)
The Matai'an landslide is the largest landslide event ever recorded in Taiwan, with an estimated volume of approximately 308 million m 3 . The failure resulted in the formation of a landslide dam, whose subsequent breach triggered a catastrophic flood, resulting in 19 fatalities, 5 missing persons, and 157 injuries. Multitemporal remote sensing analysis revealed obvious geomorphic precursor features prior to the landslide, with tensile cracking initiating and progressively developing following the 2024 Mw7.3 Hualien earthquake. Seismic source inversion analysis further indicated that the Matai'an landslide was composed of two distinct source events with different sliding directions, in which the second event predominantly involved westward motion. The two events occurred within 65 s. First, the slope collapsed, with an absolute maximum force magnitude (Fmax) of 1.995 × 10 12 N and a high sliding angle ( θ = 38.3°). Second, low-angle ( θ = 6.8°) sliding forces with an Fmax value of 0.908 × 10 12 N were resolved by seismic source inversion. This multisource failure mechanism led to stratified material deposition during landslide dam formation, a factor that critically influences the assessment of potential dam-breach mechanisms. By integrating multitemporal imagery with seismic waveform analysis, this study demonstrates that landslide-related geomorphic precursors can be detected prior to failure, while the landslide can be detected seismologically in near real time. Furthermore, the deployment of riverine seismic stations along downstream channels provides a viable approach for early warning of impending landslide-dam breach flooding.

Daidzein alleviates high-alkalinity stress-induced inflammatory liver injury in common carp by modulating gut microbiota and hepatic metabolic reprogramming - Xinchi Shang; Meiqi Xing; Xinghua Che; Shiyu Hu; Haijun Wei; Xiaodan Shi; Lanlan Zhang; Wei Xu; Longwu Geng (Aquaculture, 2026)

Urinary Fibroblast Growth Factor-23 and Soluble Alpha-Klotho in Cats with Chronic Kidney Disease - Wei-Che Chen; Wei-Li Hsu; Chao-Chin Chang; Pei-Shiue Jason Tsai; Vin-Cent Wu; Ya-Jane Lee (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Research progress on preparing CO2 adsorbents from waste materials - Yingzhe Shi; Ximiao Liu; Hualong Zhou; Wentao Guo; Zichang Che; Wei Su; Yi Xing (Journal of Environmental Chemical Engineering, 2026)

Assessing earthquake-induced displacements of large-scale landslide by in-situ monitoring and discrete element analysis - Meng-Chia Weng; Wei-An Chao; Che-Ming Yang; Tee-Ann Teo; Kuo-Wei Li; Yu-Ting Hsiao (Engineering Geology, 2026)

Al surface doping strategy enables manganese ion sieve to improve structure stability and adsorption capacity toward lithium extraction - Shibo Zhao; Yuxin Tu; Yaxin Che; Meilin Liu; Wei Wei; Zhifeng Xu; Hui Liu; Zhilou Liu (Chemical Engineering Journal, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Evolution and Challenges of Marine Oil Spill Governance in Taiwan over Two Decades - Chih-Wei Chang; Shiau-Yun Lu; Chun-Pei Liao; Wen-Yan Chiau; Yi-Che Shih (Oceans, 2026)
Marine oil spills pose critical challenges to environmental sustainability and socioeconomic stability. Taking four pivotal cases as the entry point, this study uses comparative case analysis, semi-structured stakeholder interviews, policy analysis and international gap comparison to systematically analyze the evolution of marine oil spill governance in the Taiwan region of China over two decades, aiming to identify systemic gaps and propose actionable reforms. By integrating and explicitly detailing these multiple methodologies, this research not only identifies but also systematically examines the Taiwan region of China’s unique challenges as a non-UN-member entity navigating international conventions like the international convention for the prevention of pollution from ships, 1973, as modified by the protocol of 1978 relating thereto (MARPOL 73/78). Key findings reveal persistent issues in decision-support tools, fragmented inter-agency coordination, and legal inadequacies in compensation mechanisms. The study’s novelty lies in its rigorous synthesis of localized case-driven insights compared with global best practices, proposing a concrete, phased model for a unified task force and context-aware, data-driven contingency plans to enhance real-time response efficiency. It further advocates for pragmatic steps to align the Taiwan region of China’s Marine Pollution Control Act with international standards while critically addressing the transboundary collaboration barriers imposed by its political status, exploring potential pathways through sub-national and regional partnerships. Notably, the 2023 Angel Container case underscores the urgency of modernizing enforcement capacities and integrating advanced technologies. By bridging gaps in governance, legal accountability, and practical international engagement, this research not only advances the Taiwan region of China’s preparedness but also offers a nuanced and adaptable blueprint for coastal regions facing similar geopolitical and environmental constraints. Its recommendations hold significant implications for global marine pollution management, emphasizing the interplay of policy innovation, technological adoption, and pragmatic cross-jurisdictional cooperation.

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

Long Hypocotyl 1 mediates nitrogen regulation of flowering time and nitrogen use efficiency - Xingliang Duan; Guanjie Wang; Qinglin Song; Jiale Liu; Huilin Ding; Jing Che; Wei Xuan (Plant Science, 2026)

Rapid degradation of sulfamethoxazole with high mineralization rate and energy-efficiency via C@Co/NF anode-activated peroxymonosulfate - Chuangchuang Li; Xiaoxuan Fan; Gengyuan Zhang; Runren Jiang; Chuncheng Chen; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2026)

Using ChatGPT to Solve Clinical Radiobiology Problems - Che-Wei Su; Kun-Yao Dai; Yu-Jen Chen; Yung-Shuo Kao (Journal of Cancer Education, 2026)

Formation mechanisms of foraminifera-dominated silt–sand sheets in the Baiyun Sag, South China Sea: The role of Kuroshio and North Pacific Intermediate Water - Chengkun Deng; Xiaojie Wei; Zhiqian Gao; Tailiang Fan; Zhongtao Zhang; Ronald J. Steel; Leyi Xu; Hairong Wang; Haojie Gao; Tiangui Che; Lingxue Peng (Marine Geology, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Volatile odor characterization of electrohydrodynamically (EHD) dried garlic products based on HS-GC-IMS and HS-SPME-GC-MS - Peng Guan; Wei Zuo; Zhiqing Song; Chuanqiang Che; Hao Chen; Yun Jia; Chunxu Qin; Jingli Lu; Changjiang Ding (Food Research International, 2026)

Decipher fouling's microscale hydrodynamic conditions around hollow fiber vibrating membrane - Lingping Zhang; Dawei Yu; Shujuan Che; Yuansong Wei (Desalination, 2026)

Engineering active oxygen vacancy sites in WO3@COF for efficient photocatalytic hydrogen peroxide production - Yuheng Zhang; Qixin Pan; Chaojie Xing; Jiali Lu; Yunkai Sun; Xiaoqiang Xue; Wei Wang; Che Zhao; Rui Wang (Chemical Engineering Journal, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

Gut Microbiota Dysbiosis and LPS/NLRP3/GSDMD Pyroptosis Drive Hepatic Fibrosis: Therapeutic Potential of a Synbiotic Intervention - Yuxin Che; Yangjun Shi; Yanyan Xu; Shufen Guo; Haixia Liu; Jiaojiao Yang; Jialu Liu; Jinhuan Niu; Wei Shi; Linzhi Guo; Xiaohui Wang; Fan Zhang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Role of NOX4 and GSH in Cadmium-Induced Renal Redox Homeostatic Dysregulation of Rats and APO Intervention Effect Study - Zhaofan Long; Langqiu Wei; Che Wang; Ningxi Wang; Li Song; Qiling Liu; Chuandao Shi (Biological Trace Element Research, 2026)

Phosphorus Enrichment Rewires Viral-Mediated Phosphorus Cycling in Freshwater Ecosystems via Auxiliary Metabolic Genes - Raoqiong Che; Shiying Zhang; Hao Yi; Jun Li; Kaixin Diao; Xiaolong Cui; Hongchen Jiang; Wei Xiao (Journal of Earth Science, 2026)

Structure–reactivity relationships in UV/chlorine degradation, NDMA formation, and cytotoxicity of chlorpheniramine and doxylamine - Shih-Wen Peng; Pei-Jin Lin; Ya-Hong Lin; Che-Hsin Lee; Yu-Chun Tseng; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

The rupture process of the September 2022 Guanshan and Chishang Earthquakes: Joint inversion of seismological and geodetic data - Wei-Yu Zhang; Yu-Sheng Sun; Yopi Serhalawan; Po-Fei Chen; Ming-Che Hsieh; Wu-Lung Chang (Journal of Asian Earth Sciences, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

Hydraulic characteristics of short-distance fishway and their influence on fish upstream migration behavior - Wei Yang; Liwei Tan; Xianbin Zhang; Xuan Che; Ziyue Zhu; Geng Li (Ecological Engineering, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Transcriptomics reveals that curcumin alleviates alkalinity stress-induced brain damage and neurotoxicity - Xinchi Shang; Zhaoqi He; Xinghua Che; Meiqi Xing; Longwu Geng; Lu Xing; Lanlan Zhang; Xiaohua teng; Wei Xu; Jianhong Li (Aquaculture, 2026)

Mechanism of flotation separation of fluorite from calcite using amino trimethylphosphonic acid as a novel depressant - Wenfang Che; Fen Jiao; Qian Wei; Chao Huang (Minerals Engineering, 2026)

Robust Cu₂O-NiO-Pd interfaces enabling high-yield and long-term CO₂-to-CO conversion via reverse water-gas shift reaction - Amisha Beniwal; Wei-Hao Hsiung; Che Yan; Tsan-Yao Chen; Dinesh Bhalothia (Journal of Environmental Chemical Engineering, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

A novel strategy for sodium reduction in salted goose: Employing basic amino acids to mitigate oxidation and improve sensory quality - Di Liu; Ran Wang; Zhenwei Wang; Che Shen; Qi Jin; Changhong Wu; Dekuan Wei; Kezhou Cai; Baocai Xu (Food Chemistry, 2026)

Micronutrient uptake, partitioning and accumulation in cotton under drip irrigation with mulch in response to phosphorus application in root morphology changes - Yue Ma; Zupeng Ye; Wei Li; Juanhong Wang; Qingxuan Che; Qinghui Wang; Bolang Chen; Gu Feng (Field Crops Research, 2026)

Adaptive filtering suppression method of substation environmental noise based on fast transversal least mean square algorithm - Y. Gong; H. Fan; X. Wei; K. Liu; X. Xu; K. Che; D. Li (International Journal of Environmental Science and Technology, 2026)

Acute impairments in glucose tolerance following one night of partial sleep restriction are not rescued by moderate-intensity walking in young men - Che-Wei Hsu; Chieh-Sheng Tseng; Richard S. Metcalfe; Yung-Chih Chen (European Journal of Applied Physiology, 2026)

Multi-proxy reconstruction of Holocene sedimentary evolution in the Yangtze Delta: Climatic forcing, sea-level oscillations, and diagenetic overprint - Zixuan Che; Chunzhu Chen; Lisi Wei; Wenwei Zhao; Quan Li; Yunpeng Yang; Hanfei Yang; Zhigang Wang; Xiaojian Zhang; Ximing Zhang; Shutong Yang; Huan Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ferrous-driven microbial synergy enhances reductive dechlorination under sulfide stress - Che-Wei Lu; Po-Sheng Kuo; Ku-Fan Chen; Chih-Ching Chien; Chih-Ming Kao; Ssu-Ching Chen (Journal of Hazardous Materials, 2026)

Highly isolated interlayer Co-N4 fixed by heptazine promotes peroxymonosulfate activation to selectively generate singlet oxygen - Xiang Li; Bo Liu; Shi Zhou; Chunbo Liu; Guangbo Che; Wei Jiang (Journal of Hazardous Materials, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Biochar-assisted detoxification of groundwater trichloroethene: Mitigating vinyl chloride accumulation and environmental risks via Dehalococcoides mccartyi-containing consortium - Che-Wei Lu; Ku-Fan Chen; Ching-Wen Tsai; Chao-Ling Yao; Ssu-Ching Chen (Journal of Environmental Management, 2026)

Proteomic profiling of Monascus-fermented djulis (Chenopodium formosanum) identifies ACE-inhibitory peptides through integrated in silico and in vitro approaches - Jheng-Jhe Lu; Kuan-Chen Cheng; Darin Khumsupan; Chen-Che Hsieh; Chang-Wei Hsieh; Shella Permatasari Santoso; Artik Elisa Angkawijaya; Hsing-Chun Kuo (Food Chemistry, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Engineering Mesenchymal Stem Cell-Derived Extracellular Vesicles for the Treatment of Chronic Kidney Diseases - Hsiu-Jung Liao; Kai-Hsiang Shu; Wei-Che Yu; Yen-Ling Chiu (Tissue Engineering and Regenerative Medicine, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Inhibitory regulation of glutamate release from rat cortical nerve terminals by thymoquinone - Mao-Hsiang Hsiao; Kun‑Chieh Yeh; Ming-Yi Lee; Wei-Che Chiu; Su-Jane Wang (NeuroToxicology, 2025)

Increased sensitivity of snow phenology to temperature in unstable snow regions since 1990 - Qunqun Li; Xufeng Wang; Wei Wei; Zongxing Li; Tao Che (Journal of Hydrology, 2025)

Machine learning-integrated SERS platform based on Au Se nanowires for indigo carmine detection in real samples - Nazar Riswana Barveen; Che-Wei Zeng; Yu-Wei Cheng (Food Chemistry, 2025)

Cobalt single-atom bonded perylene diimide-based linear polymer promotes photocatalytic peroxymonosulfate activation for sulfamethoxazole degradation - Guanqi Wang; Yuhang Deng; Tao Sun; Shi Zhou; Guangbo Che; Chunbo Liu; Wei Jiang (Chemical Engineering Journal, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

Investigate the protective effects of eicosapentaenoic acid in human astrocytes of oxidative stress damage and explore its underlying mechanisms - Che-Sheng Chu; Ying-Tso Chen; Wei-Chih Sun; Wei-Zhe Liang (Molecular Biology Reports, 2025)

Assessment of AOD Simulation by Assimilating Himawari and MODIS Products - Zhilin Wang; Yarong Li; Jianjun He; Wei Tian; Tie Dai; Hong Wang; Huizheng Che (Journal of Meteorological Research, 2025)

Evaluation of the working performance of different digging shovels based on the maize root-soil complex model - Hailong Che; Hua Zhou; Zhengzhong Li; Xian Wang; Xianliang Wang; Zhongcai Wei; Yanjun Li; Yinping Zhang (Biosystems Engineering, 2025)

Corrigendum to ‘Chronic Cr(VI) exposure-induced biotoxicity involved in liver microbiota-gut axis disruption in Phoxinus lagowskii Dybowski based on multi-omics technologies’ [Environ. Pollut., 368 (2025) 125759] - Xinchi Shang; Xinghua Che; Kai Ma; Wenxue Guo; Shanshan Wang; Zhi Peng Sun; Wei Xu; Yongquan Zhang (Environmental Pollution, 2025)

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Decisive electrocatalyst of oxyphilic transition metals with bivalent metal perovskites: Localized oxygen confinement for enhanced 2e-WOR in H₂O₂ production - Chemeda Barasa Guta; Chia-Yu Chang; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Endalkachew Asefa Moges; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2025)

Low-carbon competitiveness of cities in solid waste disposal systems: Spatial and temporal variations in greenhouse gas emissions in the Yangtze River Delta - Haoyu Zhang; Jicui Cui; Wei Liu; Lei Che; Wangyang Tian; Ziyang Lou (Waste Management, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Evolution mechanism of thermo-mechanical properties and microstructure of foamed cement regulated by water-based drilling cuttings content - Lidi Huang; Jieran Che; Wei Jiang; Xingyu Li; Qing Li; Shijie Fan; Yandong Liu (Process Safety and Environmental Protection, 2025)

Unraveling the flavor formation mechanisms of Wanxi dry-cured goose: Microbiomics, metabolomics, and flavoromics study - Ran Wang; Di Liu; Zhenwei Wang; Changhong Wu; Che Shen; Jingnan Lu; Wen Nie; Dekuan Wei; Kezhou Cai; Baocai Xu (Food Research International, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

Carbon nitride featuring a robust built-in electric field with ultra-high photocatalytic activity - Yue Xu; Tianyu Zhou; Wei Jiang; Bo Hu; Chunbo Liu; Guangbo Che (Chemical Engineering Journal, 2025)

Theoretical calculations to identify and design transition metal-based additives for hydrogen storage materials - Thi Thu Le; Jiangming Cao; Svetlana Korneychuk; Wei-che Chang; Marcus Willi Rackel; Denis Kramer; Jürgen Markmann; Fahim Karimi; Astrid Pundt; Thomas Klassen; Claudio Pistidda (Chemical Engineering Journal, 2025)

Multi-level metalized PBO composite fabric for polar extreme environments: integrating electromagnetic protection, stable electric thermal conversion, and high-strength - Che Zhou; Dan Yu; Canglong Xing; Zhichao Zhu; Zeyu Yang; Xinhai He; Tao Fu; Zhongxiao Song; Wei Fan; Dongzhen Chen (Chemical Engineering Journal, 2025)

Carbon-water nexus of China's iron and steel industry through CCUS technology development - Wei Su; Ximiao Liu; Jinglei Tian; Saige Wang; Yi Xing; Zichang Che; Juan Liu (Journal of Cleaner Production, 2025)

Spatiotemporal dynamics of histone H3K27 demethylase during development - Yu-Chen Tsai; Yun-Chen Chung; Cheng-Chan Yang; Cheng-Hsien Lee; Che-Wei Liu; Shih-Ming Huang; Lan-Hsin Wang (Insect Biochemistry and Molecular Biology, 2025)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

Effects of using deep learning to predict the geographic origin of barley genebank accessions on genome–environment association studies - Che-Wei Chang; Karl Schmid (Theoretical and Applied Genetics, 2025)
Genome–environment association (GEA) is an approach for identifying adaptive loci by combining genetic variation with environmental parameters, offering potential for improving crop resilience. However, its application to genebank accessions is limited by missing geographic origin data. To address this limitation, we explored the use of neural networks to predict the geographic origins of barley accessions and integrate imputed environmental data into GEA. Neural networks demonstrated high accuracy in cross-validation but occasionally produced ecologically implausible predictions as models solely considered geographical proximity. For example, some predicted origins were located within non-arable regions, such as the Mediterranean Sea. Using barley flowering time genes as benchmarks, GEA integrating imputed environmental data ( $$N=11,032$$ N = 11 , 032 ) displayed partially concordant yet complementary detection of genomic regions near flowering time genes compared to regular GEA ( $$N=1,626$$ N = 1 , 626 ), highlighting the potential of GEA with imputed data to complement regular GEA in uncovering novel adaptive loci. Also, contrary to our initial hypothesis anticipating a significant improvement in GEA performance by increasing sample size, our simulations yield unexpected insights. Our study suggests potential limitations in the sensitivity of GEA approaches to the considerable expansion in sample size achieved through predicting missing geographical data. Overall, our study provides insights into leveraging incomplete geographical origin data by integrating deep learning with GEA. Our findings indicate the need for further development of GEA approaches to optimize the use of imputed environmental data, such as incorporating regional GEA patterns instead of solely focusing on global associations between allele frequencies and environmental gradients across large-scale landscapes.

Chemical constituents of the aerial parts of Mitracarpus hirtus (L.) DC (Rubiaceae) - Xinyi Wei; Yingrun Ma; Mingming Xu; Ding Heng; Monday M. Onakpa; Jin-Ao Duan; Chun-Tao Che; Hongkai Bi; Junfei Zhou; Ming Zhao (Natural Product Research, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

Estimating the Permeability–Depth Relation of Slate Formation for Geothermal Project - Xuan-Xinh Nguyen; Che-Wei Yeh; Tan-Minh Le; Jia-Jyun Dong; Chih-Hsi Liu; Chi-Ping Pan (Rock Mechanics and Rock Engineering, 2025)

Design, synthesis and anti-oomycete activity of 2-acyloxyhinokitiol derivatives - Ruxue Wei; Yibo Liu; Wanying Yin; Ruiguang Wang; Yuee Tian; Xiaobo Huang; Le Qian; Shengming Liu; Genqiang Chen; Zhiping Che (Natural Product Research, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Mechanistic insights into chloroethene dechlorination by Dehalococcoides mccartyi strain CWV2: A multi-omics perspective - Chih-Ming Kao; Ku-Fan Chen; Po-Sheng Kuo; Chih-Ching Chien; Che-Wei Lu; Ssu-Ching Chen (Water Research, 2025)

Mitigating and adapting to extreme climate: Developing a novel assessment model for unexplained hot-humid exposure in metropolitan areas - Yuqian Guo; Xiwei Shen; Yifeng Qin; Shengquan Che; Minghao Wei; Ling Wang (Sustainable Cities and Society, 2025)

Field experiment study to assess critical wave conditions leading to failure of mangrove Rhizophora stylosa - Nobuhito Mori; Che-Wei Chang; Kenji Ono; Hironori Noguchi; Shigeyuki Baba; Hideaki Yanagisawa; Toyohiko Miyagi; Naoki Tsuruta; Kojiro Suzuki; Shiro Yamagata; Yusuke Hasegawa; Yu-Lin Tsai; et al. (Coastal Engineering, 2025)

Twelve strategies for realizing the promise of ecopracticology - Steven J. Cooke; Marco Carlotti; Kgosietsile Velempini; Nathan Heavers; Zhifang Wang; Zoe Moula; Qinghe Hou; Andrew Howarth; Meagan Harper; Andrew N. Kadykalo; Yasuhisa Kondo; Yue Che; et al. (Socio-Ecological Practice Research, 2025)

Effects of monochromatic LED light quality on photosynthetic capacity and pigment content in Dunaliella salina under low light intensity - Tianze Zhao; Yongfu Li; Xingkai Che; Haixing Wu; Yuchen Ye; Dingning Fan; Zhendong Li; Yingjie Zhao; Wei Ye (Journal of Applied Phycology, 2025)

Improving the Antifouling Properties of CTD During the Marine Field Tests: The Use of CAP@MMT Modified with Acid - Yachen Che; Lianxue Wei; Yaqi Diao; Wenjuan Jia; Hongzhi Li (Journal of Ocean University of China, 2025)

Associations between pesticides in honeybees/hive products and adjacent land use in a rural region of Taiwan - Chien-Che Hung; Chung-Wen Hsueh; Wei-Cheng Chang; Lih-Ming Yiin (Science of The Total Environment, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

Synthesis of novel 18 β -glycyrrhetinic acid sulfonate derivatives displaying significant anti-oomycete activity against Phytophthora capsici - Yibo Liu; Yan Li; Yuee Tian; Yihao Guo; Ruxue Wei; Xiaobo Huang; Le Qian; Shengming Liu; Genqiang Chen; Zhiping Che (Natural Product Research, 2025)

Research progress and future prospects of chemical utilization of CO2 - Yingzhe Shi; Wei Su; Yi Xing; Yongkang Cui; Ximiao Liu; Wentao Guo; Zichang Che (Chemical Engineering Journal, 2025)

Surface Wave Numerical Simulation and Characteristics Analysis Considering the Effect of Sea Ice in the Bohai Sea, China - Wenbo Li; Zhifeng Wang; Rui Li; Che Yue; Wei Zhang; Shengjian Chen (Pure and Applied Geophysics, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Uncertainty Analysis of Overflow Due to Sea Dike Failure During Typhoon Events - Wei-Che Huang; Wen-Cheng Liu; Hong-Ming Liu (Journal of Marine Science and Engineering, 2025)
Taiwan is frequently affected by typhoons, which cause storm surges and wave impacts that damage sea dikes, resulting in overflow and subsequent flooding. Therefore, it is essential to analyze the damage to sea dikes caused by storm surges and wave impacts, leading to overflow, for effective coastal protection. This study employs the ADCIRC model coupled with the SWAN model to simulate storm surges and waves around Taiwan and develops a sea dike failure model that incorporates mechanisms for impact damage, run-up damage, and overflow calculation. To ensure model accuracy, three historical typhoon events were used for calibration and validation of the ADCIRC+SWAN model. The results show that the ADCIRC coupled with SWAN model can effectively simulate storm surges and waves during typhoons. Typhoon Soulik (2013) was simulated to examine a breach in the Tamsui Youchekou sea dike in northern Taiwan, and an uncertainty analysis was conducted using the Monte Carlo method and Bayesian theorem. The results indicate that when the compressive strength of the sea dike is reduced to 5% of its original strength, impact and run-up damage occur, leading to overflow. In the case of impact damage, the overflow volume due to the breach falls within a 95% confidence interval of 0.16 × 106 m3 to 130 × 106 m3. For run-up damage, the 95% confidence interval for the overflow volume ranges from 0.16 × 106 m3 to 639 × 106 m3. The ADCIRC+SWAN model is used to simulate storm surge and waves, incorporating impact damage and run-up damage mechanisms to represent concrete sea dike failure. This approach effectively models dike failure and calculates the resulting overflow.

Release characteristics of arsenic from sediments and its source or sink competition with phosphorus: A case of a great lake with grass-algae alternation - Shuhang Wang; Yongsheng Chang; Wei Huang; Dianhai Yang; Feifei Che (Journal of Environmental Sciences, 2025)

Chronic Cr(VI) exposure-induced biotoxicity involved in liver microbiota-gut axis disruption in Phoxinus lagowskii Dybowski based on multi-omics technologies - Xinchi Shang; Xinghua Che; Kai Ma; Wenxue Guo; Shanshan Wang; Zhi Peng Sun; Wei Xu; Yongquan Zhang (Environmental Pollution, 2025)

Olaparib research update: mechanism, structure and clinical trials - Hao Che; Li-Wei Wang; Xiang-Yang Ye; Xingrui He (Medicinal Chemistry Research, 2025)

Land degradation decreased crop productivity by altering soil quality index generated by network analysis - Ming Gao; Wei Hu; Xingyi Zhang; Meng Li; Yongsheng Yang; Renfeng Che (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Anthropogenic drought monitoring using socio-hydrological modeling for surface water deficit: Lessons from Northern Taiwan - Che-You Liu; Pin-Yi Huang; Shao-Yiu Hsu; Ching-Pin Tung; Kuo-Wei Liao (Journal of Hydrology, 2025)

Ignition study of hypergolic solid fuels through counterflow experiment using hydrogen peroxide spray - Wei-Che Lin; Gregory Young (Fuel, 2025)

Eco-friendly lamellar structured graphene oxide-Lysine nanocomposite membranes with varying d-spacing for enhanced pervaporation desalination - Shalligito Habetamu Abebe; Hannah Faye M. Austria; T.M. Subrahmanya; Huai-Che Chang; Tsung-Han Huang; Gabriel V. Carballo; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Epidemiology of liver diseases: global disease burden and forecasted research trends - Jia Xiao; Fei Wang; Yuan Yuan; Jinhang Gao; Lu Xiao; Chao Yan; Feifei Guo; Jiajun Zhong; Zhaodi Che; Wei Li; Tian Lan; Frank Tacke; et al. (Science China Life Sciences, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

SPH simulations to investigate the influence of realistic mangroves in reducing breaking wave forces on coastal structures - Shengzhe Wang; Che-Wei Chang (Ocean Engineering, 2025)

Hybrid Laplace-time domain model for coupled dynamic analysis of multibody mating system in topside float-over installations - Wei Tao; Jinwei Sun; Shuqing Wang; Jupeng Che; Yuhao Wei (Ocean Engineering, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Black soldier fly and microbiome collaborate to bioconvert the tofu whey water in an efficient and environment-friendly manner - Xiaowen Ji; Shaojie Zhou; Wenwen Chen; Bin Cao; Yumeng Sun; Qiyang Che; Yinglao Zhang; Jibin Zhang; Ting Ding; Jiaping Xu; Feng Peng; Maoye Li; et al. (Journal of Water Process Engineering, 2025)

Mechanical properties and interfacial adhesion mechanism of polyolefin composites reinforced with ethylene vinyl alcohol-coated cellulose microfibers - Yixin Zhao; Shuya Zhang; Lei Zhang; Mingda Che; Renliang Huang; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Selenium-enriched Lactobacillus plantarum alleviate of high alkalinity-induced microbiota-gut-blood systems affect by improving the gut microbiota - Xinchi Shang; Longwu Geng; Haijun Wei; Xinghua Che; Lu Xing; Meiqi Xing; Wei Xu; Jian Hong Li (Aquaculture, 2024)

Environmental changes and human impacts over the past 1200 years: Evidence from high-resolution pollen records from peat in the Yunnan-Guizhou Plateau, Southwest China - Shuming Li; Lisi Wei; Wenwei Zhao; Weihe Ren; Qinran Gu; Zixuan Che; Xianyong Cao; Huan Li; Xiaojian Zhang; Chunzhu Chen; Yan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Comparative analysis of element and hormone content in zygotic embryos of Pinus elliottii and P. elliottii × P. caribaea - Yang Liu; Lei Xue; Zhe Wang; Xiaoliang Che; Leping Deng; Wei Xie; Wenbing Guo (Journal of Plant Physiology, 2024)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

Investigation of discharge valve in ultra-high-speed rotary compressors: An experimental and FSI simulation-based study - Hua Zhong; Wei Zhao; Zhaodong Zhang; Che Wang; Keke Gao; Jianhua Wu (International Journal of Refrigeration, 2024)

Analyzing Dehalochip: A functional DNA microarray for reductive dichlorination in chloroethene-contaminated sites - Che-Wei Lu; Chih-Ming Kao; Chao-Ling Yao; Ssu-Ching Chen (Environmental Pollution, 2024)

A Kirkendall strategy for the efficient degradation of trichloroethylene from groundwater using cellulose nanofiber-supported sulfidated nZVI - Mingda Che; Jingzhe Xiao; Shuya Zhang; Cancan Shan; Ze Zhao; Renliang Huang; Yitong Zhou; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2024)

In enzymatic reactions, the reverse reaction reduces product noise - Ching-Chu Hsieh; Yung-Chun Lin; Wei-Bo Lin; Che-Chi Shu (BioSystems, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

A BP-Neural-Network-Based PID Control Algorithm of Shipborne Stewart Platform for Wave Compensation - Daoxi Li; Shuqing Wang; Xiancang Song; Zepeng Zheng; Wei Tao; Jvpeng Che (Journal of Marine Science and Engineering, 2024)
In order to carry out offshore operations smoothly in severe sea conditions, a shipborne Stewart platform for wave compensation is required. Due to the random characteristics of waves, traditional control algorithms cannot accurately compensate for the motion caused by a wave. For the electric shipborne Stewart platform, this paper proposes a backpropagation (BP)-neural-network-based proportional–integral–derivative (PID) control algorithm where the PID parameters are adaptively adjusted by a BP neural network. The control algorithm can improve the robustness and wave compensation precision of the wave compensation system. First, a numerical system model of the shipborne Stewart platform was established according to the classical kinematic model and dynamic model. Then, the BP-PID control algorithm was designed based on the joint space control. In order to reduce the network’s sensitivity to local details and quickly find the global minimum, the gradient descent method with the momentum term is used in the neural network. At last, the availability and rationality of the new method were substantiated through a simulation comparison under various sea conditions. The simulation results indicate that the proposed control method achieves a higher compensation accuracy in three directions under various sea states, compared with traditional PID control algorithm. Under the irregular wave disturbance, the new control method can reduce the position deviation by about 6.56 times compared with a traditional PID control algorithm. The new control algorithm will play an active role in the control of the shipborne Stewart platform.

Fungal necromass contribution to carbon sequestration in global croplands: A meta-analysis of driving factors and conservation practices - Dong Liu; Ziyan Zhou; Shahid Iqbal; Ting Ting Dou; Gregory Bonito; Wei Liu; Shaoshan An; Caspar C.C. Chater; Jesus Perez-Moreno; Rongxiao Che; Davey L. Jones; Fuqiang Yu (Science of The Total Environment, 2024)

Novel electrocatalyst with abundant oxygen vacancies enabling efficient two-electron water oxidation reaction for H2O2 synthesis - Chemeda Barasa Guta; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Chia-Yu Chang; Fikiru Temesgen Angerasa; Endalkachew Asefa Moges; Yosef Nikodimos; Keseven Lakshmanan; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2024)

Microhabitat-differentiated distribution of culturable and antagonistic bacteria in marine ecosystem: Seawater as the original microbial provider - Yuhan Che; Ziqiao Feng; Decheng He; Feifei Cao; Xing Chen; Aiyou Huang; Yanhua Zeng; Hao Long; Xiaoni Cai; Wei Ren; Zhenyu Xie (Ocean & Coastal Management, 2024)

Graphene oxide nanosheets reinforced quaternized poly(2,6-dimethyl-1,4-phenylene oxide) composite membranes with enhanced hydroxide ions conduction at subzero temperature - Xiaoqing Wei; Tingting Zuo; Dan Wu; Niuniu Zhang; Xinna Gao; Quantong Che (Journal of Environmental Chemical Engineering, 2024)

Synergistic Triple-Action morphological composite Anode: Integrating lattice Softening, Interfacial electric Fields, and dual confinement for superior Potassium-Ion battery performance - Jia-Sheng Lin; Yi-Yen Hsieh; Kai-Yuan Hsiao; Yi-Chun Yang; Che-Hung Wang; Ming-Yen Lu; Wen-Wei Wu; Hsing-Yu Tuan (Chemical Engineering Journal, 2024)

The adsorption and fixation of Cd and Pb by the microbial consortium weakened the toxic effect of heavy metal-contaminated soil on rice - Songhao Che; Jianing Wang; Yuanqin Zhou; Chengcai Yue; Xueying Zhou; Yufeng Xu; Shiqi Tian; Zhenning Cao; Xiaoshuang Wei; Siyuan Li; Xue Yang; Zhihai Wu; et al. (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Highly-separated Co anchored on S, O-doped carbon nitride for enhanced peroxymonosulfate activation: Insights into radical and non-radical pathways - Yuhang Deng; Simiao Wang; Tianyu Zhou; Bo Liu; Bo Hu; Liang Wang; Chunbo Liu; Wei Jiang; Guangbo Che (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Coseismic and subsequent landslides of the 2024 Hualien earthquake (M7.2) on April 3 in Taiwan - Jui-Ming Chang; Wei-An Chao; Che-Ming Yang; Ming-Wan Huang (Landslides, 2024)

Tropical cyclone ensemble forecast framework based on spatiotemporal model - Tongfei Li; Kaihua Che; Jiadong Lu; Yifan Zeng; Wei Lv; Zhiyao Liang (Earth Science Informatics, 2024)

Factors influencing mangrove carbon storage and its response to environmental stress - Chuanyi Guo; Pei Sun Loh; Jianxiong Hu; Zengxuan Chen; Siriporn Pradit; Chantha Oeurng; Ty Sok; Che Abd Rahim Mohamed; Choon Weng Lee; Chui Wei Bong; Xixi Lu; Gusti Z. Anshari; et al. (Frontiers in Marine Science, 2024)
Mangrove forests serve as significant carbon sinks and play a crucial role in mitigating climate change. Currently, the response of mangroves to intensified climate change and human activities, and the factors that influence the magnitude of carbon storage in their sediments remain uncertain. To address these questions, two sediment cores were collected from the mangrove reserve in Pearl Bay, Guangxi, China. The activity of 210 Pb in the sediment, grain size, bulk elemental composition, stable carbon isotopes, lignin, and different sediment organic matter (OM) fractions were investigated to determine the local mangrove’s response to climate change and human activities, as well as the factors influencing its carbon storage. The results showed mangrove forests with lower tidal ranges, slower sedimentation rates, and where OM predominantly originated locally tend to have larger carbon stocks. The mangrove OM (MOM) decreased progressively from the bottom to the top of the cores, indicating that the mangroves in Pearl Bay have possibly undergone degradation, which was further substantiated by the decrease in lignin content. Based on these results, the entire cores were divided into two stages: stable stage 1 (1963–2001) and degradation stage 2 (2001–2020). The cause of the mangrove degradation is likely due to the impact of human activities; however, these impacts are anticipated to gradually lessen in the future due to mangrove protection policies. Our results indicate that lignin can track and predict mangrove growth trends and provide guidance for the sustainable management of mangrove ecosystems.

China's gray zone actions in the East China Sea, Taiwan Strait, and South China Sea: A comparative study and impact on fisheries - Wei-Chung Chen; Ching-Hsiewn Ou; Ming-Hao Yang; Yi-Che Shih (Marine Policy, 2024)

Improve flotation efficiency of refractory tungsten ore and reduce carbon emission in flotation process: A case study of Sandaozhuang deposit in Henan, China - Wei Li; Fen Jiao; Xu Wang; Wenfang Che; Zhengquan Zhang; Baijun Xin; Min Xu; Wenqing Qin (Minerals Engineering, 2024)

Spray combustion characteristics and soot formation potential of Nano-Al2O3 diesel at low ambient temperatures - Zhefeng Guo; Che-Wei Wu; Yee-Lin Wu; Yen-Yi Lee; Sheng-Lun Lin; Timothy H. Lee (Fuel, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Exploring the highly efficient depressant role of fenugreek gum on talc in chalcopyrite flotation - Yuhang Che; Wei Chen; Sheng Liu; Guangsheng Zeng; Guangyi Liu (Minerals Engineering, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Circ_0090231 knockdown protects vascular smooth muscle cells from ox-LDL-induced proliferation, migration and invasion via miR-942-5p/PPM1B axis during atherosclerosis - Jian Yang; Xiangyan Li; Yuming Zhang; Pengfei Che; Wei Qin; Xuecui Wu; Yue Liu; Bing Hu (Molecular and Cellular Biochemistry, 2024)

Repetitive Administration of Low-Dose Lipopolysaccharide Improves Repeated Social Defeat Stress-Induced Behavioral Abnormalities and Aberrant Immune Response - Vichuda Charoensaensuk; Wei-Lan Yeh; Bor-Ren Huang; Tsung-Che Hsu; Sheng-Yun Xie; Chao-Wei Chen; Yu-Wen Wang; Liang-Yo Yang; Cheng-Fang Tsai; Dah-Yuu Lu (Journal of Neuroimmune Pharmacology, 2024)

Effect of plasma activated water Immersion on Broccoli Seed Germination and Nutritional Quality of Sprouts - Gongheng Che; Ting Jiang; Xiaodan Li; Junxia Xiao; Liang Liu; Jianteng Wei; Liping Guo (Journal of Plant Growth Regulation, 2024)

Vibration Suppression of Two Adjacent Cables Using an Interconnected Tuned Mass Damper/Nonlinear Energy Sink - Che Yao; Dejian Li; Xiaojun Wei (Journal of Marine Science and Engineering, 2024)
Due to their high flexibility, low damping, and small mass, stay cables are prone to large-amplitude vibrations. Various mechanical measures, typically installed near the cable anchorage to the deck, have been developed to suppress cable vibration. These dampers, however, may not be effective for ultralong cables since the damper is close to the cable anchorage, the cable node. In this paper, a tuned mass damper (TMD)/nonlinear energy sink (NES) are considered for installation between two adjacent stay cables for vibration mitigation. Firstly, the static equilibrium equation of the stay cable–damper system is established, and the influence of the self-weight of the damper on cable shape is investigated. The governing equations describing the motion of the two adjacent cables with a damper are then established using the Hamilton principle, which are then solved by the method of separation of variables. For cases of swept-sine excitation and harmonic excitation, the optimal designs of TMD and NES are achieved with the purpose of suppressing the first- and third-mode-dominated vibrations, respectively. Both optimal TMD and NES may substantially suppress cable vibrations, with each having advantages under certain situations. Finally, the dynamic response characteristics of two adjacent cables with an optimal damper are analyzed. Interesting dynamic behaviors, such as energy input suppression, phase shift, cable frequency shift, and phase diagram boundary rotation, are identified, and their mechanisms are explained.

Novel magnetic N-doped biochar derived from sugarcane bagasse and red mud for effective adsorption of tetracycline hydrochloride - Linye Zhang; Jun Xiao; Huixian Che; Deyuan Xiong; Yanling Zhou; Baiying Li; Yi Liu; Guangtao Wei (Journal of Environmental Chemical Engineering, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Self-reconstructed ZIF-L/Co(OH)2 heterointerface modulates electronic structure of Ru and boosts electrocatalytic hydrogen evolution - Xinhui Yu; Yi Chen; Yuanyuan Wu; Xianyu Chu; Bo Liu; Bo Hu; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

Experimental study on sewage collection and related performance of square arc angle aquaculture tank - Zonglong Che; Yinxin Zhou; Chenxu Zhao; Xiaozhong Ren; Hangfei Liu; Wei Sun; Haibo Liu; Meng Li (Aquaculture International, 2024)

Artificial neural network-based multi-input multi-output model for short-term storm surge prediction on the southeast coast of China - Yue Qin; Zilu Wei; Dongdong Chu; Jicai Zhang; Yunfei Du; Zhumei Che (Ocean Engineering, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Excavatolide C/cisplatin combination induces antiproliferation and drives apoptosis and DNA damage in bladder cancer cells - Tsu-Ming Chien; Che-Wei Yang; Chia-Hung Yen; Bi-Wen Yeh; Wen-Jeng Wu; Jyh-Horng Sheu; Hsueh-Wei Chang (Archives of Toxicology, 2024)

An innovative permeable reactive bio-barrier to remediate trichloroethene-contaminated groundwater: A field study - Che-Wei Lu; Kai-Hung Lo; Sun-Chong Wang; Chih-Ming Kao; Ssu-Ching Chen (Science of The Total Environment, 2024)

Novel Multiplexed High Throughput Screening of Selective Inhibitors for Drug-Metabolizing Enzymes Using Human Hepatocytes - Jianhua Liu; Daria Vernikovskaya; Gary Bora; Anthony Carlo; Woodrow Burchett; Samantha Jordan; Lloyd Wei Tat Tang; Joy Yang; Ye Che; George Chang; Matthew D. Troutman; Li Di (The AAPS Journal, 2024)

Characterization of phosphate solubilizing bacteria in the sediments of eutrophic lakes and their potential for cyanobacterial recruitment - Chengqi Tu; Xiaoshuang Dong; Haoran Yang; Yongsheng Chang; Zhongshuo Xu; Feifei Che; Shuhang Wang; Wei Huang (Chemosphere, 2024)

Storage and dynamics of soil organic carbon in allochthonous-dominated and nitrogen-limited natural and planted mangrove forests in southern Thailand - Jianxiong Hu; Siriporn Pradit; Pei Sun Loh; Zengxuan Chen; Chuanyi Guo; Thi Phuong Quynh Le; Chantha Oeurng; Ty Sok; Che Abd Rahim Mohamed; Choon Weng Lee; Chui Wei Bong; Xixi Lu; et al. (Marine Pollution Bulletin, 2024)

Driving effects of dissolved organic carbon on cadmium release of the sediments by cyanobacterial decomposition - Shuhang Wang; Yongsheng Chang; Dianhai Yang; Wei Huang; Feifei Che (Journal of Water Process Engineering, 2024)

Characterization of CYP3A5 Selective Inhibitors for Reaction Phenotyping of Drug Candidates - Jie Chen; Lloyd Wei Tat Tang; Samantha Jordan; Makayla Harrison; Gabrielle M. Gualtieri; Ethan DaSilva; Danial Morris; Gary Bora; Ye Che; Li Di (The AAPS Journal, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

Assessing the effect of input motion duration on seismic site responses of layered soil deposits using spectrally equivalent records - Wei Che; Wenhao Wang; Zhaofan Chen; Shixuan Ye (Soil Dynamics and Earthquake Engineering, 2024)

Occurrence characteristics and risk assessment of microplastics in agricultural soils in the loess hilly gully area of Yan' an, China - Zhifeng Jia; Wei Wei; Yanhua Wang; Yingjie Chang; Rui Lei; Yanhong Che (Science of The Total Environment, 2024)

Fluvial flood adaptation using nature-based solutions: A comprehensive and effective assessment of hydro-meteorological risks - Kuo-Wei Liao; John Thedy; Chun-Che Tai (Science of The Total Environment, 2024)

Detection of surface defects for maize seeds based on YOLOv5 - Yu Xia; Tianci Che; Jingwu Meng; Jinghao Hu; Gengle Qiao; Wenbo Liu; Jie Kang; Wei Tang (Journal of Stored Products Research, 2024)

Enhanced mitigation of inhalable particles and fine particle-bound PAHs from a novel hazardous waste-power plant candidate - Wei Tang; Che-Wei Wu; Sheng-Lun Lin; Jhong-Lin Wu; Shih-Wei Huang; Mengjie Song (Environmental Pollution, 2024)

Using a Laboratory Column Experiment to Explore the Influence of an Antecedent Dry Period on the Nutrient Removal of a Bioretention Filter - Wei Zhang; Zimeng Zhuang; Juan Li; Huichao Sun; Wu Che (Water, Air, & Soil Pollution, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Response mechanism of sediment endogenous phosphorus release to functional microorganisms and its cyanobacterial growth and disappearance effects - Wei Huang; Xiaoshuang Dong; Chengqi Tu; Haoran Yang; Yongsheng Chang; Xixi Yang; Haojie Chen; Feifei Che (Science of The Total Environment, 2024)

In situ preparation of biochar/Bi4O5Br2 composite for ibuprofen removal under the synergistic effect of adsorption and photocatalysis and the underlying mechanism - Huanxian Shi; Yumiao Zhang; Yueyue Wei; Chen Che; Zhanyang Xia; Guolong Li; Xiaofei Zhang; Yajun Shi; Zhishu Tang (Journal of Water Process Engineering, 2024)

The coupled effect of sediment resuspension and microbiota on phosphorus release and transformation in a simulated aquatic ecosystem - Haoran Yang; Yongsheng Chang; Xiaoshuang Dong; Shuhang Wang; Feifei Che; Wei Huang (Journal of Water Process Engineering, 2024)

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Portable and reversible smart labels for non-destructive detection of seafood freshness via amine-response fluorescent ionic liquids - Siying Che; Shujia Pan; Xinxiang Shao; Wei He; Qijia Shou; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Interfacial C-O covalent bonds improving the piezo-assisted photocatalytic performance of Bi4Ti3O12@Carbon Schottky heterojunction - Kun Zhou; Wei Liu; Peifang Wang; Juan Chen; Huinan Che; Bin Liu; Yanhui Ao (Chemical Engineering Journal, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

A study on photocatalytic Janus membrane reactor for direct conversion of low concentration carbon dioxide in air to methane: Effects of combination of two-dimensional carbon nanosheets - Chien-Chieh Hu; Ya-Chiao Chen; Eyasu Gebrie Ajebe; Meng-Che Tsai; Wei-Song Hung; Hsieh-Chih Tsai; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Phenomic Imaging - Lizhen Lan; Kai Feng; Yudan Wu; Wenbo Zhang; Ling Wei; Huiting Che; Le Xue; Yidan Gao; Ji Tao; Shufang Qian; Wenzhao Cao; Jun Zhang; et al. (Phenomics, 2023)
Human phenomics is defined as the comprehensive collection of observable phenotypes and characteristics influenced by a complex interplay among factors at multiple scales. These factors include genes, epigenetics at the microscopic level, organs, microbiome at the mesoscopic level, and diet and environmental exposures at the macroscopic level. “Phenomic imaging” utilizes various imaging techniques to visualize and measure anatomical structures, biological functions, metabolic processes, and biochemical activities across different scales, both in vivo and ex vivo. Unlike conventional medical imaging focused on disease diagnosis, phenomic imaging captures both normal and abnormal traits, facilitating detailed correlations between macro- and micro-phenotypes. This approach plays a crucial role in deciphering phenomes. This review provides an overview of different phenomic imaging modalities and their applications in human phenomics. Additionally, it explores the associations between phenomic imaging and other omics disciplines, including genomics, transcriptomics, proteomics, immunomics, and metabolomics. By integrating phenomic imaging with other omics data, such as genomics and metabolomics, a comprehensive understanding of biological systems can be achieved. This integration paves the way for the development of new therapeutic approaches and diagnostic tools.

Begonia locbaosangii (Begoniaceae), a handsome new species from Lang Son Province, North Vietnam - Danh Duc Nguyen; Che-Wei Lin (Kew Bulletin, 2023)

Spatiotemporal variations and influential factors affecting reproductive dynamics of Pacific saury in the Northwest Pacific during fishing season - Wei‐Che Hung; Jhen Hsu; Yi‐Jay Chang; Wen‐Bin Huang; Chih‐Hao Hsieh; Ming‐Tsung Chung (Journal of Fish Biology, 2023)
This study examined the spatial and monthly variations in reproductive dynamics of Pacific saury collected in the high sea (40°N−49°N, 149°E−168°E) of the northwestern Pacific during the fishing season of the Taiwanese stick‐held dip‐net fisheries (July–November) from 2018 to 2019. Generalized additive mixed‐effects models (GAMMs) were applied to explore the relationship between the probability of maturing and spawning occurrence ( P MOS ) and the explanatory variables (month, body length, sea‐surface temperature [SST] as fixed effects, and fishing set as a random effect) for the age 0 and age 1 fish, respectively. In addition, the impact of the geographical difference in growth rates of age 0 fish, quantified as the radius of the otolith annual ring, on the P MOS of age 1 fish was explored in the GAMMs. Results showed that the mean values of the condition factor (CF) varied by months, and higher mean CFs were observed north of 45°N. However, the mean values of the gonado‐somatic index did not show a clear spatiotemporal pattern. The spatial distribution of the ovarian maturation states revealed that the spawning ground of Pacific saury during July–November was broader than that previously known and had partly overlapped with the high‐sea fishing ground. The best GAMM showed that the predicted P MOS of the age 0 fish were generally low (mean = 19%, standard deviation [SD] = 10%) and tended to increase with increasing body length. In contrast, the predicted P MOS were relatively higher (mean = 37%, SD = 10%) for the age 1 fish and increased with increasing SST and decreasing latitude. Two candidate GAMMs, which are equally supported as the best model (ΔAIC

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Suppressing thermal runaway propagation of nickel-rich Lithium-ion battery modules using silica aerogel sheets - Jin Tang; Xinyuan Wu; Jian Ren; Huihua Min; Xiaomin Liu; Yong Kong; Peipei Che; Wei Zhai; Hui Yang; Xiaodong Shen (Process Safety and Environmental Protection, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Structurally diverse (9β-H)-pimarane derivatives with six frameworks from the leaves of Icacina oliviformis and their cytotoxic activities - Mingming Xu; Di Di; Lu Fan; Yingrun Ma; Xinyi Wei; Er-Xin Shang; Monday M. Onakpa; Oluwatosin O. Johnson; Jin-Ao Duan; Chun-Tao Che; Junfei Zhou; Ming Zhao (Phytochemistry, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Tannic acid enhanced the removal of Phaeocystis globosa from seawater by Fe (II) activated persulfate - Mingda Che; Xianfeng Wang; Mei Cui; Renliang Huang; Wei Qi; Rongxin Su (Journal of Environmental Chemical Engineering, 2023)

Strong variation of near-surface seismic anisotropy in Taiwan and its geological implications - Hsin-Yu Lee; Yuancheng Gung; Li-Wei Chen; Wen-Shan Chen; Ying-Nien Chen; Sheng-Jyun Cai; Hui-Chu Chen; Che-Wei Liao (Earth and Planetary Science Letters, 2023)

A rebuttal to “Response to “Feremycorrhizal fungi: A confusing and erroneous term”: Feremycorrhiza means ‘nearly mycorrhiza’; hence, it is a clear and correct term because the fungal partner has mycorrhizal traits and lineage” - Christopher P. Chanway; Akshit Puri; Kiran Preet Padda; Che-Wei Chang (Biology and Fertility of Soils, 2023)

Image-based recognition and processing system for monitoring water levels in an irrigation and drainage channel - Wen-Cheng Liu; Chun-Kai Chung; Wei-Che Huang (Paddy and Water Environment, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Efficient removal of chloroform from groundwater using activated percarbonate by cellulose nanofiber-supported Fe/Cu nanocomposites - Mingda Che; Jingzhe Xiao; Cancan Shan; Shaohuang Chen; Renliang Huang; Yitong Zhou; Mei Cui; Wei Qi; Rongxin Su (Water Research, 2023)

Performance and mechanism of a novel biopolymer binder for clayey soil stabilization: Mechanical properties and microstructure characteristics - Jin Liu; Wenyue Che; Xiaowei Lan; Mengyuan Hu; Mengyao Qi; Zezhuo Song; Mengya Sun; Miao Jing; Wei Qian; Changqing Qi (Transportation Geotechnics, 2023)

Field experiments: How well can seismic monitoring assess rock mass falling? - Jui-Ming Chang; Wei-An Chao; Yu-Ting Kuo; Che-Ming Yang; Hongey Chen; Yu Wang (Engineering Geology, 2023)

Gorgeous turn-back: Rough surface treatment strategy induces Cu-C and N-C active moieties for bifunctional oxygen electrocatalysis - Shuai Wang; Zhongmei Che; Min Zou; Yue Wu; Min Cui; Yingshu Guo; Mingrui Zhang; Wei Hu; Zihan Zou; Guangqiang Lv; Zexing Wu; Jeonghun Kim; et al. (Chemical Engineering Journal, 2023)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

High-entropy transition metal disulfide colloid clusters: synergistic atomic scale interaction and interconnected network for ultra-stable potassium ion storage - Yan-Jie Liao; Wei-Wen Shen; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

The effect of maternal consumption of high-fat diet on ovarian development in offspring - Wenyan Wei; Feng Qin; Junjie Gao; Junlei Chang; Xujing Pan; Xuemei Jiang; Lianqiang Che; Yong Zhuo; De Wu; Shengyu Xu (Animal Reproduction Science, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

Accelerating proton conduction in proton exchange membranes with sandwich structure based on carbon nanotubes oxide - Ke Liu; Shu Hu; Xiaoqing Wei; Tingting Zuo; Quantong Che (Process Safety and Environmental Protection, 2023)

Depth Profiles of Microplastic in Sediment Cores in the Mangrove Area of Kuala Gula Mangrove, Malaysia - Che Abd Rahim Mohamed; Aqilah Nur Shahruddin; Siriporn Pradit; Pei Sun Loh; Thongchai Nitiratsuwan; Thawanrat Kobkeatthawin; Prakrit Noppradit; Thi Phuong Quynh Le; Chantha Oeurng; Ty Sok; Choon Weng Lee; Chui Wei Bong; et al. (Journal of Marine Science and Engineering, 2023)
Microplastics are widespread in coastal and marine environments, and sediments serve as a sink for microplastics. In this study, four sediment cores were collected from the Kuala Gula Mangrove area. The abundance of microplastics in mangrove sediments ranged from 25–130 items/kg dry weight. The highest abundance of microplastic was observed at the KG04 site near the mouth of the river. The number of microplastics by sampling site was significantly different (p 0.05). However, this study provides evidence that mangroves can be a trap for microplastics and can be used as baseline data for future studies.

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Super facile one-step synthesis of sugarcane bagasse derived N-doped porous biochar for adsorption of ciprofloxacin - Huixian Che; Guangtao Wei; Zuodan Fan; Youlian Zhu; Linye Zhang; Zhaozhou Wei; Xinlan Huang; Linru Wei (Journal of Environmental Management, 2023)

Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor - Chen-Che Hsieh; Shu-Han Yu; Kai-Wen Cheng; Yu-Wei Liou; Cheng-Chih Hsu; Chang-Wei Hsieh; Chia-Hung Kuo; Kuan-Chen Cheng (Food Research International, 2023)

Investigating spatio-temporal variability of initial 230Th/232Th in intertidal corals - Hong-Wei Chiang; Belle Philibosian; Aron J. Meltzner; Chung-Che Wu; Chuan-Chou Shen; R. Lawrence Edwards; Chih-Kai Chuang; Bambang W. Suwargadi; Danny H. Natawidjaja (Quaternary Science Reviews, 2023)

Hindcasting and predicting surge heights and waves on the Taiwan coast using a hybrid typhoon wind and tide-surge-wave coupled model - Wen-Cheng Liu; Wei-Che Huang (Ocean Engineering, 2023)

Highly anti-interference electrocatalytic sensing for dopamine with nitrogen-doped graphdiyne directly in biofluids - Min Cui; Peicheng Xin; Zhongmei Che; Min Zou; Mingrui Zhang; Xiaofeng Sun; Yanan Yuan; Zihan Zou; Guangqiang Lv; Shuai Wang; Wei Hu (Chemical Engineering Journal, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

Resistance risk assessment of Fusarium pseudograminearum from wheat to prothioconazole - Jiangqiao Wei; Xuhao Guo; Jia Jiang; Le Qian; Jianqiang Xu; Zhiping Che; Xiaobo Huang; Shengming Liu (Pesticide Biochemistry and Physiology, 2023)

The development of ocean governance for marine environment protection: Current legal system in Taiwan - Yi-Che Shih; Wei Chung Chen; Tai-An Peter Chen; Chih-wei Chang (Frontiers in Marine Science, 2023)
Taiwan establishes Ocean Affairs Council (OAC) in 2018. Ocean governance has reached a new milestone. In 2019, the Ocean Basic Act was enacted. In 2020, the National Ocean Policy White Paper was published, meaning that Taiwan has specialized ocean authorities, regulations, enforcement units, and relevant mechanisms and policies. The Ocean Conservation Administration (OCA) is also responsible for marine environmental protection and conservation. To ensure good ocean governance, maintain marine resources, and protect the environment, the OCA has recently drafted the Marine Conservation Act for sustainable development. This article mainly reviews, analyzes, and compares Taiwan’s current marine-related laws and regulations and refers to the laws, policies, and mechanisms of other countries to provide suggestions on marine governance and the ongoing draft of the Marine Conservation Act.

Impact of plant community structure and its diversity on richness and abundance of arthropod aphidophagous natural enemy community - Jian-hong Wang; Bin-bin Ren; Jin-li Shao; Wei Li; Shao-cheng Che (Urban Forestry & Urban Greening, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

First report of Rhizoctonia solani AG-4 HG-I causing leaf blight disease on Cattleya × hybrid in Taiwan - Ya-Chu Hsieh; Che-Wei Chang; Chao-Jen Wang (Journal of General Plant Pathology, 2023)

Dietary Selenium-Rich Lactobacillus plantarum Alleviates Cadmium-Induced Oxidative Stress and Inflammation in Bulatmai barbel Luciobarbus capito - Qing Zhang; Xinchi Shang; Longwu Geng; Xinghua Che; Haijun Wei; Shizhan Tang; Wei Xu (Fishes, 2023)
Cadmium (Cd) poses a great threat to the breeding of aquatic economic animals. The present study aimed to explain the antagonistic effects of selenium-enriched Lactobacillus plantarum (SL) on Cd toxicity through the expression of oxidative and inflammatory factors. A total of 225 Bulatmai barbel Luciobarbus capito (L. capito) were divided into 3 groups, namely, the control group, the Cd group (Cd, 0.05 mg·L−1), and the SL + Cd group (Cd, 0.05 mg·L−1; Nano Se, 5 mg·kg−1; L. plantarum, 105 CFU·g−1). The experiment lasted for 28 d, Sampling at 14 and 28 d, respectively. The results showed that Cd exposure caused obvious pathological damage to the liver and kidney, and the serum parameter ALT increased significantly (p

Correction to: Differential plasma protein expression after ingestion of essential amino acid-based dietary supplement versus whey protein in low physical functioning older adults - Gohar Azhar; Ambika Verma; Xiaomin Zhang; Amanda Pangle; Pankaj Patyal; Wei Zhang; Yingni Che; Karen Coker; Robert R. Wolfe; Jeanne Y. Wei (GeroScience, 2023)

Evaluation of the antimicrobial mechanism of biogenic selenium nanoparticles against Pseudomonas fluorescens - Ying Xu; Ting Zhang; Jiarui Che; Jiajia Yi; Lina Wei; Hongliang Li (Biofouling, 2023)

Efficient removal of Phaeocystis globosa from seawater with the persulfate activation by arbutin-modified cellulose nanocrystals - Mingda Che; Cancan Shan; Wenjie Zhang; Yanyi Duan; Renliang Huang; Mei Cui; Wei Qi; Rongxin Su (Chemosphere, 2023)

Study on the management efficiency of lanthanum/iron co-modified attapulgite on sediment phosphorus load - Yihe Qu; Li Zhao; Zhenghai Jin; Haoran Yang; Chengqi Tu; Feifei Che; Mohammad Russel; Xinshan Song; Wei Huang (Chemosphere, 2023)

Toxicity prediction: An application of alternative testing and computational toxicology in contaminated groundwater sites in Taiwan - Rachelle D. Arcega; Rong-Jane Chen; Pei-Shan Chih; Yi-Hsuan Huang; Wei-Hsiang Chang; Ting-Khai Kong; Ching-Chang Lee; Trias Mahmudiono; Chun-Chih Tsui; Wen-Che Hou; Hsin-Ta Hsueh; Hsiu-Ling Chen (Journal of Environmental Management, 2023)

SO2 resistance of CeO2- and Co3O4-supported activated carbon during removal of mercury from flue gas: A comparative study - Shengji Wu; Yalun Ma; Wangsheng Yu; Hui Wang; Wei Yang; Lei Che; Zhongxi Han (Fuel, 2023)

Thiophanate-methyl induces notochord toxicity by activating the PI3K-mTOR pathway in zebrafish (Danio rerio) embryos - Xiaofang Che; Yong Huang; Keyuan Zhong; Kun Jia; You Wei; Yunlong Meng; Wei Yuan; Huiqiang Lu (Environmental Pollution, 2023)

Thermodegradation characterization of microplastics: Dispersion effect and pyrolysis kinetics by artificial intelligence - Wei-Hsin Chen; Shih-Che Sun; Jherwin B. Ocreto; Thanh-Binh Nguyen; Su Shiung Lam; Young-Kwon Park; Cheng-Di Dong (Chemical Engineering Journal, 2023)

Oxygen vacancies endow atomic cobalt-palladium oxide clusters with outstanding oxygen reduction reaction activity - Thomas Yang; Dinesh Bhalothia; Hong-Wei Chang; Che Yan; Amisha Beniwal; You-Xun Chang; Shun-Chi Wu; Po-Chun Chen; Kuan-Wen Wang; Sheng Dai; Tsan-Yao Chen (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Differential plasma protein expression after ingestion of essential amino acid-based dietary supplement verses whey protein in low physical functioning older adults - Gohar Azhar; Ambika Verma; Xiaomin Zhang; Amanda Pangle; Pankaj Patyal; Wei Zhang; Yingni Che; Karen Coker; Robert R. Wolfe; Jeanne Y. Wei (GeroScience, 2023)
In a recent randomized, double-blind, placebo-controlled trial, we were able to demonstrate the superiority of a dietary supplement composed of essential amino acids (EAAs) over whey protein, in older adults with low physical function. In this paper, we describe the comparative plasma protein expression in the same subject groups of EAAs vs whey. The plasma proteomics data was generated using SOMA scan assay. A total of twenty proteins were found to be differentially expressed in both groups with a 1.5-fold change. Notably, five proteins showed a significantly higher fold change expression in the EAA group which included adenylate kinase isoenzyme 1, casein kinase II 2-alpha, Nascent polypeptide-associated complex subunit alpha, peroxiredoxin-1, and peroxiredoxin-6. These five proteins might have played a significant role in providing energy for the improved cardiac and muscle strength of older adults with LPF. On the other hand, fifteen proteins showed slightly lower fold change expression in the EAA group. Some of these 15 proteins regulate metabolism and were found to be associated with inflammation or other comorbidities. Gene Ontology (GO) enrichment analysis showed the association of these proteins with several biological processes. Furthermore, protein–protein interaction network analysis also showed distinct networks between upregulated and downregulated proteins. In conclusion, the important biological roles of the upregulated proteins plus better physical function of participants in the EAAs vs whey group demonstrated that EAAs have the potential to improve muscle strength and physical function in older adults. This study was registered with ClinicalTrials.gov: NCT03424265 “Nutritional interventions in heart failure.”

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

Effects of sand incorporation and temperatures on desiccation cracks, moisture dynamics, and microstructure evolution of sandy slopes’ topsoil at multi-scales - Zi Wang; Jin Liu; Fan Bu; Wenyue Che; Zezhuo Song; Ke Ma; Wei Qian (Bulletin of Engineering Geology and the Environment, 2023)

Mercury cycling and isotopic fractionation in global forests - Xun Wang; Wei Yuan; Che-Jen Lin; Xinbin Feng (Critical Reviews in Environmental Science and Technology, 2022)

Assessing the impact of rockfall on the retaining structures of a mountain road: a case study in Taiwan - Che-Ming Yang; Chung-Hsun Lee; Chun-Yuan Liu; Wei-Kai Huang; Meng-Chia Weng; Yu-Yao Fu (Landslides, 2022)

Metabolic trade-offs associated with homeostatic adjustments in pelagic and benthic cephalopods: Comparative evaluations of NH4+/H+ transport machinery in gills - Meng-Wei Lin; Pou-Long Kuan; Po-Hsuan Sung; Yung-Che Tseng (Frontiers in Marine Science, 2022)
Cephalopods are ancient mollusks that can be found in many different ecological niches in the ocean ranging from the intertidal zone to the deep-sea abyss. In order to adapt to a lifestyle in various habitats, cephalopods have evolved a variety of locomotory modes to accommodate their respective habitats. Most cephalopods have relatively high metabolic rates due to their less efficient swimming mode by jet propulsion. This lifestyle is characterized by a high level of energy expenditure, fueled exclusively by protein diets that are rapidly digested and may produce metabolic nitrogenous waste NH 3 / NH 4 + accumulation and acid-base disturbances. This study observed that the NH 4 + transport rate in pelagic bigfin reef squid (Sepioteuthis lessoniana) is two times faster than benthic common octopus ( Octopus vulgaris ). Inhibition of Na + /H + exchangers (NHEs) showed significant disruption of NH 4 + and H + excretory processes in gills of octopus but not in squid. However, inhibition of vacuolar-type H + -ATPase (VHA) significantly disrupts NH 4 + and H + transport rates in gills of both animals. Accordingly, for NH 4 + and H + homeostasis, benthic octopus with lower aerobic respiration rates utilize both active and Na + -driven secondary transport machinery. In order to avoid NH 4 + accumulated in the blood, pelagic squids with higher aerobic respiration rates prefer active NH 4 + and H + transport mechanisms that consume ATP intensively.

Brain structural connectivity sub typing in unilateral temporal lobe epilepsy - Zhensheng Li; Che Jiang; Wei Xiang; Zijuan Qi; Quwen Gao; Kairun Peng; Jian Lin; Wei Wang; Weimin Wang; Bingmei Deng (Brain Imaging and Behavior, 2022)

Shallow-water hydrothermal vent system as an extreme proxy for discovery of microbiome significance in a crustacean holobiont - Ling Chiu; Min-Chen Wang; Kuang-Yu Tseng; Chih-Lin Wei; Huei-Ting Lin; Shan-Hua Yang; Yung-Che Tseng (Frontiers in Marine Science, 2022)
The shallow-water hydrothermal vent (HV) system off Kueishan Island lies at the end of the Okinawa Trough to the northeast of Taiwan. Near its submarine vent openings, aperiodic vent discharges generate a dynamic acidic (pH 5.5-8.1) and sulfidic (9-3000 μM) ecosystem. The dominant metazoan in this unique environment is the brachyuran vent crab, Xenograpsus testudinatus , which has developed robust metabolic strategies and highly adaptive acid-base regulatory mechanisms to maintain its physiological homeostasis. X. testudinatus is considered a holobiont, but the symbiotic mechanisms underlying acid and sulfur tolerance in the host-microbe system remain largely unclear. In this study, we used LoopSeq long-read sequencing of the full-length 16S rRNA gene to identify the bacterial communities present in the gills and carapace surface of X. testudinatus . The alpha diversity analysis, Venn diagram, and principal coordinate analysis (PCoA) indicated that the gills and carapace surface exhibit different bacterial constituents. Further measurements of relative abundance, coupled with functional predictions and fluorescence in situ hybridization (FISH), revealed a predominance of Sulfurovum sp. NBC37-1, a key bacterium that can perform sulfur and hydrogen oxidation to support denitrification processes. Consequently, our findings suggest that the symbiotic bacteria may play a critical role in conferring the extraordinary acid and sulfur tolerances of X. testudinatus , allowing the crustacean holobiont to thrive in its ecological niche within one of the most extreme marine habitats on Earth.

Transcriptome analysis reveals the effects of strigolactone on shoot regeneration of apple - Sumeera Asghar; Yao Xiong; Meng Che; Xingqiang Fan; Hui Li; Yi Wang; Xuefeng Xu; Wei Li; Zhenhai Han (Plant Cell Reports, 2022)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

POLLEN STERILITY, a novel suppressor of cell division, is required for timely tapetal programmed cell death in rice - Ronghui Che; Bin Hu; Wei Wang; Yunhua Xiao; Dapu Liu; Wenchao Yin; Hongning Tong; Chengcai Chu (Science China Life Sciences, 2022)

The Impact of the Antipsychotic Medication Chlorpromazine on Cytotoxicity through Ca2+ Signaling Pathway in Glial Cell Models - Che-Sheng Chu; Yung-Shang Lin; Wei-Zhe Liang (Neurotoxicity Research, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

Response of bacterial communities in saline-alkali soil to different pesticide stresses - Juan Che; Yan Lei Zhu; Yan Hong Li; Rui Zhang; Zhi Yong Ruan; Wei Zhang (Environmental Science and Pollution Research, 2022)

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Life span of a landslide dam on mountain valley caught on seismic signals and its possible early warnings - Che-Ming Yang; Jui-Ming Chang; Chi-Yao Hung; Chih-Heng Lu; Wei-An Chao; Keng-Hao Kang (Landslides, 2022)
Outburst flooding after a landslide dam breach causes global fatalities and devastation. Information on the timing, magnitude, and location of the landslide dam is crucial to hazard assessment. Despite recent efforts, successful real-time detection of landslide dams in mountain valleys and dam breakages is rare. Here, we present a series of seismic analysis including landslide detection, identification of landslide dam formations, and monitoring of dam breaches. We show the working of our analysis on a recent landslide dam that occurred in eastern Taiwan. The results indicate that our seismic analysis provides important information on the location and magnitude of landslides and the dam forming based on data acquired from a regional broadband seismic network. Furthermore, we see that the failure of the landslide dam is directly caught by the riverside seismic signals. To provide warning times for impending floods to downstream areas, we believe that proximal high-quality seismic signals along the river channel are viable options for an operational real-time monitoring system, for landslide dams occurring in mountain valleys. Our work can be a starting point to raise awareness in the community.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

On-Site Investigations of Coastal Erosion and Accretion for the Northeast of Taiwan - Ting-Yu Liang; Chih-Hsin Chang; Shih-Chun Hsiao; Wei-Po Huang; Tzu-Yin Chang; Wen-Dar Guo; Che-Hsin Liu; Jui-Yi Ho; Wei-Bo Chen (Journal of Marine Science and Engineering, 2022)
Coastal erosion is a major natural hazard along the northeastern shoreline (i.e., Yilan County) of Taiwan. Analyses of the evolution of the 0 m isobath of the Yilan County coastline indicate that erosion and accretion are occurring north and south of Wushi Fishery Port, respectively, because of jetty and groin construction. Topographic and bathymetric surveys involving the measurement of 43 cross sections were conducted in 2006, 2012, 2013, and 2019. The cross-shore profile comparisons reveal that the erosion of onshore dunes is significant in the northern Jhuan River estuary. Due to the establishment of a nature reserve in the southern Lanyang River estuary, the sediments are carried northward by tidal currents, and accretion is inevitable in the northern Lanyang River estuary. The results of the bathymetric surveys also suggest that the shoreline of Yilan County tends to accrete in summer because of abundant sediment from the rivers; however, it is eroded in winter, owing to the large waves induced by the northeast monsoon. Additionally, the calculated net volume of erosion and accretion between each pair of cross sections shows that the length of coastline impacted by estuarine sediment transport is approximately 2 km long from north to south along the coastline of the Lanyang River estuary.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Rapid changes to glaciers increased the outburst flood risk in Guangxieco Proglacial Lake in the Kangri Karpo Mountains, Southeast Qinghai-Tibetan Plateau - Yanjun Che; Shijin Wang; Yanqiang Wei; Tao Pu; Xinggang Ma (Natural Hazards, 2022)

The regenerating protein 3A: a crucial molecular with dual roles in cancer - Liying Wang; Yanchun Quan; Yanxi Zhu; Xiaoli Xie; Zhiqiang Wang; Long Wang; Xiuhong Wei; Fengyuan Che (Molecular Biology Reports, 2022)
Introduction REG3A, a member of the third subclass of the Reg family, has been found in a variety of tissues but is not detected in immune cells. In the past decade, it has been determined that REG3A expression is regulated by injury, infection, inflammatory stimuli, and pro-cytokines via different signaling pathways, and it acts as a tissue-repair, bactericidal, and anti-inflammatory molecule in human diseases. Recently, the role of REG3A in cancer has received increasing attention. The present article aims to investigate the structure, expression, regulation, function of REG3A, and to highlight the potential role of REG3A in tumors. Methods A detailed literature search and data organization were conducted to find information about the role of REG3A in variety of physiological functions and tumors. Results Contradictory roles of REG3A have been reported in different tumor models. Some studies have demonstrated that high expression of REG3A in cancers can be oncogenic. Other studies have shown decreased REG3A expression in cancer cells as well as suppressed tumor growth. Conclusions Taken together, better understanding of REG3A may lead to new insights that make it a potentially useful target for cancer therapy.

Microbacterium sulfonylureivorans sp. nov., isolated from sulfonylurea herbicides degrading consortium - Qingyun Ma; Delong Kong; Qi Zhang; Miaomiao Li; Xiaoyan Han; Juan Che; Yiqing Zhou; Wei Zhang; Xu Jiang; Zhiyong Ruan (Archives of Microbiology, 2022)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Experimental investigation and discrete element method simulation on mechanical properties and failure mechanism of polymer-stabilized sand - Wenyue Che; Jin Liu; Hongyang Li; Chengzong He; Yuxia Bai; Zezhuo Song; Ying Wang; Wei Qian; Zhihao Chen (Bulletin of Engineering Geology and the Environment, 2022)

Distribution and Catch Rate Characteristics of Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in Relation to Oceanographic Factors in the Waters Around Taiwan - Lu-Chi Chen; Jinn-Shing Weng; Muhamad Naimullah; Po-Yuan Hsiao; Chen-Te Tseng; Kuo-Wei Lan; Che-Chen Chuang (Frontiers in Marine Science, 2021)
This study investigated the relationship of the catch rates (CRs) of Spanish mackerel ( Scomberomorus commerson ) with oceanographic factors in the waters around Taiwan by using high-resolution fishery and environmental data for the period 2011–2016. The investigation results revealed that trammel nets accounted for 69.79% of the total catch of S. commerson and were operated mostly in the Taiwan Strait (TS). We noted seasonal variations in the distribution of high CRs. These CRs were observed in the southwestern TS, including the waters along the southwestern coast of Taiwan and around the Penghu Islands, and extended to the Taiwan Bank during autumn; they increased in winter. To predict the spatial and temporal patterns of Spanish mackerel density and their relationship with oceanographic and spatiotemporal variables, generalized additive models were used. These models explained 48.4% of the total deviance, which was consistent with the assumed Gaussian distribution. Moreover, all variables examined were significant CR predictors ( p < 0.05). Latitude and longitude were the key factors influencing the spatiotemporal distribution of S. commerson , and sea surface chlorophyll a concentration was a key oceanographic factor. Observing projected changes in El Niño/Southern Oscillation events for S. commerson revealed that CRs were higher and distributed further southward during La Niña events than during other events. We inferred that the S. commerson distribution gradually moved toward the southwest with the northeast monsoon, which was enhanced during La Niña in winter.

High chloroform removal using tannic acid to promote the activation of persulfate with Fe/Ni nanoparticles - Mingda Che; Zhiguo Chen; Sha Qiu; Mei Cui; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2021)

Critical Risk Indicators (CRIs) for the electric power grid: a survey and discussion of interconnected effects - Judy P. Che-Castaldo; Rémi Cousin; Stefani Daryanto; Grace Deng; Mei-Ling E. Feng; Rajesh K. Gupta; Dezhi Hong; Ryan M. McGranaghan; Olukunle O. Owolabi; Tianyi Qu; Wei Ren; Toryn L. J. Schafer; et al. (Environment Systems and Decisions, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

The severe toxicity of CuO nanoparticles to the photosynthesis of the prokaryotic algae Arthrospira sp - Xingkai Che; Ruirui Ding; Qiang Zhang; Yujie Li; Qi Sun; Yuting Li; Zishan Zhang; Wei Wang; Huiyuan Gao (Environmental Science and Pollution Research, 2021)

Efficient removal of chloroform in groundwater by polyethylene glycol-stabilized Fe/Ni nanoparticles - Huimin Si; Mingda Che; Zhiguo Chen; Sha Qiu; Mei Cui; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

Tide–surge and wave interaction around the Taiwan coast: insight from Typhoon Nepartak in 2016 - Wen-Cheng Liu; Wei-Che Huang (Natural Hazards, 2021)

Schizocorticium gen. nov. (Hymenochaetales, Basidiomycota) with three new species - Sheng-Hua Wu; Chia-Ling Wei; Yu-Ping Chen; Che-Chih Chen; Siou-Zhen Chen (Mycological Progress, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Translocation and distribution of mercury in biomasses from subtropical forest ecosystems: evidence from stable mercury isotopes - Yi Liu; Che-Jen Lin; Wei Yuan; Zhiyun Lu; Xinbin Feng (Acta Geochimica, 2021)

Dorsolateral Striatal proBDNF Improves Reversal Learning by Enhancing Coordination of Neural Activity in Rats - Wei Sun; Hongxia Che; Jia Li; Dongxin Tang; Xiaoyun Liu; Wenhui Liu; Lei An (Molecular Neurobiology, 2020)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Dynamic response characteristics and failure mode of slopes on the loess tableland using a shaking-table model test - Zhi-jian Wu; Duo-yin Zhao; Ai-lan Che; Da-wei Chen; Chao Liang (Landslides, 2020)

Tannic acid enhances the removal of chloroform from water using NaOH-activated persulfate - Xudong Zhao; Zhiguo Chen; Mingda Che; Sha Qiu; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2020)

Large paleo-rockslide induced by buckling failure at Jiasian in Southern Taiwan - Che-Ming Yang; Keng-Hao Kang; Shun-Hsing Yang; Kuo-Wei Li; Hui-Jung Wang; Yin-Tsan Lee; Kuei-Kun Lin; Yii-Wen Pan; Jyh-Jong Liao (Landslides, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Designing a New Endoscope for Panoramic-View with Focus-Area 3D-Vision in Minimally Invasive Surgery - Dinh Thai Kim; Ching-Hwa Cheng; Don-Gey Liu; Kai Che Jack Liu; Wayne Shih Wei Huang (Journal of Medical and Biological Engineering, 2020)
Purpose The minimally invasive surgery (MIS) has shown advantages when compared to traditional surgery. However, there are two major challenges in the MIS technique: the limited field of view (FOV) and the lack of depth perception provided by the standard monocular endoscope. Therefore, in this study, we proposed a New Endoscope for Panoramic-View with Focus-Area 3D-Vision (3DMISPE) in order to provide surgeons with a broad view field and 3D images in the surgical area for real-time display. Method The proposed system consisted of two endoscopic cameras fixed to each other. Compared to our previous study, the proposed algorithm for the stitching videos was novel. This proposed stitching algorithm was based on the stereo vision synthesis theory. Thus, this new method can support 3D reconstruction and image stitching at the same time. Moreover, our approach employed the same functions on reconstructing 3D surface images by calculating the overlap region’s disparity and performing image stitching with the two-view images from both the cameras. Results The experimental results demonstrated that the proposed method can combine two endoscope’s FOV into one wider FOV. In addition, the part in the overlap region could also be synthesized for a 3D display to provide more information about depth and distance, with an error of about 1 mm. In the proposed system, the performance could achieve a frame rate of up to 11.3 fps on a single Intel i5-4590 CPU computer and 17.6 fps on a computer with an additional GTX1060 Nvidia GeForce GPU. Furthermore, the proposed stitching method in this study could be made 1.4 times after when compared to that in our previous report. Besides, our method also improved stitched image quality by significantly reducing the alignment errors or “ghosting” when compared to the SURF-based stitching method employed in our previous study. Conclusion The proposed system can provide a more efficient way for the doctors with a broad area of view while still providing a 3D surface image in real-time applications. Our system give promises to improve existing limitations in laparoscopic surgery such as the limited FOV and the lack of depth perception.

Study on recognition of mine water sources based on statistical analysis - Enke Hou; Qiang Wen; Xiaoyang Che; Wei Chen; Jiangbo Wei; Zhenni Ye (Arabian Journal of Geosciences, 2020)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Negative regulation of aryl hydrocarbon receptor by its lysine mutations and exposure to nickel - Xun Che; Wei Dai (Molecular & Cellular Toxicology, 2019)

Hydrophobic-force-driven adsorption of bisphenol A from aqueous solution by polyethylene glycol diacrylate hydrogel microsphere - Hongxue Du; Shuyun Shi; Wei Liu; Guangbo Che; Mingyue Piao (Environmental Science and Pollution Research, 2019)

Using a numerical method to precisely evaluate the alpha angle in a hip image - Chung-Liang Lai; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Hsiao-Che Lin; Chin-Liang Kuo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2019)

Arbuscular mycorrhizal fungi abundance was sensitive to nitrogen addition but diversity was sensitive to phosphorus addition in karst ecosystems - Dan Xiao; Rongxiao Che; Xin Liu; Yongjun Tan; Rong Yang; Wei Zhang; Xunyang He; Zhihong Xu; Kelin Wang (Biology and Fertility of Soils, 2019)

Nutrient removal from urban stormwater runoff by an up-flow and mixed-flow bioretention system - Wei Zhang; Min Sang; Wu Che; Huichao Sun (Environmental Science and Pollution Research, 2019)

Sodium dodecyl sulfate-coated-cationized agroforestry residue as adsorbent for benzene-adsorptive sequestration from aqueous solution - Helen Kong; Norasikin Saman; Pei Nee Tee; Siew Chin Cheu; Shiow Tien Song; Khairiraihanna Johari; Jimmy Wei Ping Lye; Mohd Azizi Che Yunus; Hanapi Mat (Environmental Science and Pollution Research, 2019)

Identification of a major QTL on chromosome arm 2AL for reducing yellow rust severity from a Chinese wheat landrace with evidence for durable resistance - Zhen Wang; Junda Ren; Ziyi Du; Mingzhe Che; Yibin Zhang; Wei Quan; Xu Jiang; Yuan Ma; Yin Zhao; Zhongjun Zhang (Theoretical and Applied Genetics, 2019)

Detection and validation of a novel major QTL for resistance to Fusarium head blight from Triticum aestivum in the terminal region of chromosome 7DL - Junda Ren; Zhen Wang; Ziyi Du; Mingzhe Che; Yibin Zhang; Wei Quan; Yongji Wang; Xu Jiang; Zhongjun Zhang (Theoretical and Applied Genetics, 2019)

Novel Polymeric Valve for Transcatheter Aortic Valve Replacement Applications: In Vitro Hemodynamic Study - Oren M. Rotman; Brandon Kovarovic; Wei-Che Chiu; Matteo Bianchi; Gil Marom; Marvin J. Slepian; Danny Bluestein (Annals of Biomedical Engineering, 2019)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

Natural variation ofCsSTOP1in tea plant (Camellia sinensis) related to aluminum tolerance - Hua Zhao; Wei Huang; Yange Zhang; Ziwei Zhang; Yong Li; Che Tang; Jie Huang; Dejiang Ni (Plant and Soil, 2018)

Rainfall and inflow effects on soil erosion for hillslopes dominated by sheet erosion or rill erosion in the Chinese Mollisol region - Hai-ou Shen; Lei-lei Wen; Yun-feng He; Wei Hu; Hong-li Li; Xiao-cui Che; Xin Li (Journal of Mountain Science, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Studies on the Development of Small Abalone ( Haliotis diversicolor supertexta ) Essence and its Antioxidative Properties - Yu-Wei Chang; Chun-Che Lin; Wen-Chieh Sung (Journal of Aquatic Food Product Technology, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Pricing weather index insurance based on artificial controlled experiment: a case study of cold temperature for early rice in Jiangxi, China - Qing Sun; Zaiqiang Yang; Xianghong Che; Wei Han; Fangmin Zhang; Fang Xiao (Natural Hazards, 2018)

Using nonlinear finite element models to analyse stress distribution during subluxation and torque required for dislocation of newly developed total hip structure after prosthetic impingement - Wei-Min Chi; Chien-Chung Lin; Ying-Jui Ho; Hsiao-Che Lin; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2018)

Perceptions, behavioral expectations, and implementation timing for response actions in a hurricane emergency - Shih-Kai Huang; Hao-Che Wu; Michael K. Lindell; Hung-Lung Wei; Charles D. Samuelson (Natural Hazards, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Simulating and mapping the risk of surge floods in multiple typhoon scenarios: a case study of Yuhuan County, Zhejiang Province, China - Mengya Li; Wei Wu; Jun Wang; Zhumei Che; Yali Xie (Stochastic Environmental Research and Risk Assessment, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Modeling the interaction between tides and storm surges for the Taiwan coast - Wen-Cheng Liu; Wei-Che Huang; Wei-Bo Chen (Environmental Fluid Mechanics, 2016)

Double-Edged Roles of Nitric Oxide Signaling on APP Processing and Amyloid-β Production In Vitro: Preliminary Evidence from Sodium Nitroprusside - Zheng-Xu Cai; Hui-Shu Guo; Che Wang; Min Wei; Cheng Cheng; Zhao-Fei Yang; Yin-Wang Chen; Wei-Dong Le; Song Li (Neurotoxicity Research, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Theoretical Analysis of Total Hip Dislocation and Comparison of Hemispherical Cup and Newly Developed Cup - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Jian-Horng Chen (Journal of Medical and Biological Engineering, 2015)

A QTL with major effect on reducing leaf rust severity on the short arm of chromosome 1A of wheat detected across different genetic backgrounds and diverse environments - Ziyi Du; Mingzhe Che; Guohui Li; Jiang Chen; Wei Quan; Yan Guo; Zhen Wang; Junda Ren; Huyan Zhang; Zhongjun Zhang (Theoretical and Applied Genetics, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

Teaching socio-environmental synthesis with the case studies approach - Cynthia A. Wei; William R. Burnside; Judy P. Che-Castaldo (Journal of Environmental Studies and Sciences, 2015)

Mixed Integer Linear Programming Models for Selecting Ground-Level Ozone Control Strategies - Wei-Che Hsu; Jay M. Rosenberger; Neelesh V. Sule; Melanie L. Sattler; Victoria C. P. Chen (Environmental Modeling & Assessment, 2014)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

An ephaptic transmission model of CA3 pyramidal cells: an investigation into electric field effects - Xile Wei; Yinhong Chen; Meili Lu; Bin Deng; Haitao Yu; Jiang Wang; Yanqiu Che; Chunxiao Han (Cognitive Neurodynamics, 2014)

A study on rational slopeland classification for land conservation in Taiwan: a case of Jhuoshuei River before Typhoon Morakot - Chao-Wen Wang; Che-Wei Shen; Li-Ling Lin (Paddy and Water Environment, 2014)

VPA inhibits renal cancer cell migration by targeting HDAC2 and down-regulating HIF-1α - Feng-qiang Yang; Min Liu; Feng-ping Yang; Jianping Che; Wei Li; Wei Zhai; Guang-chun Wang; Jun-hua Zheng; Xi Li (Molecular Biology Reports, 2014)

Removal of Trihalomethanes and Haloacetic Acids from Treated Drinking Water by Biological Activated Carbon Filter - Jie-Chung Lou; Che-Jung Chang; Wei-Hsiang Chen; Wei-Bin Tseng; Jia-Yun Han (Water, Air, & Soil Pollution, 2014)

Stability and cytotoxicity of angiotensin-I-converting enzyme inhibitory peptides derived from bovine casein - Wei Wu; Pan-pan Yu; Feng-yang Zhang; Hong-xia Che; Zhan-mei Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Mapping of QTL conferring resistance to sharp eyespot (Rhizoctonia cerealis) in bread wheat at the adult plant growth stage - Jiang Chen; Guo Hui Li; Zi Yi Du; Wei Quan; Hu Yan Zhang; Ming Zhe Che; Zhen Wang; Zhong Jun Zhang (Theoretical and Applied Genetics, 2013)

Actinopolyspora dayingensis sp. nov., a novel halophilic actinomycete isolated from a hypersaline lake - Tong-Wei Guan; Hui-Ping Zhao; Zhen-Ming Che; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2013)

Down-regulation of eIF5A-2 prevents epithelial-mesenchymal transition in non-small-cell lung cancer cells - Guo-dong Xu; Xin-bao Shi; Le-bo Sun; Qing-yun Zhou; Da-wei Zheng; Huo-shun Shi; Yong-liang Che; Zi-shan Wang; Guo-feng Shao (Journal of Zhejiang University-SCIENCE B, 2013)

Isoptericola salitolerans sp. nov., a halotolerant filamentous actinobacterium isolated from a salt lake, China - Tong-Wei Guan; Yun Teng; Ling-Ling Yang; Xiao-Ping Zhang; Zhen-Ming Che (Extremophiles, 2013)

Effects of design parameters of total hip components on the impingement angle and determination of the preferred liner skirt shape with an adequate oscillation angle - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Field Approaches to Measure Hg Exchange Between Natural Surfaces and the Atmosphere—A Review - Jonas Sommar; Wei Zhu; Che-Jen Lin; Xinbin Feng (Critical Reviews in Environmental Science and Technology, 2013)

Myceligenerans salitolerans sp. nov., a halotolerant actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Nan Wu; Shu-Kun Tang; Zhen-Ming Che; Xiang-Gui Chen (Extremophiles, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Enhancing Effects of Chronic Lithium Treatment on Detour Learning in Chicks - Lei Zhang; Xiaoyun Chen; Wei Feng; Hui Liang; Yonghua Cui; Shiqing Xu; Yi Che (Biological Trace Element Research, 2012)

Cryptococcosis in China (1985–2010): Review of Cases from Chinese Database - Chen Yuchong; Che Fubin; Chen Jianghan; Wei Fenglian; Xu Nan; Yang Minghui; Sun Yalin; Zheng Zhizhong (Mycopathologia, 2012)

Simulation of direct radiative forcing of aerosols and their effects on East Asian climate using an interactive AGCM-aerosol coupled system - Hua Zhang; Zhili Wang; Zaizhi Wang; Qianxia Liu; Sunling Gong; Xiaoye Zhang; Zhongping Shen; Peng Lu; Xiaodong Wei; Huizheng Che; Laurent Li (Climate Dynamics, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Chemical modification and anticancer effect of prenylated flavanones from Taiwanese propolis - Chia-Nan Chen; Che-Jen Hsiao; Shoei-Sheng Lee; Jih-Hwa Guh; Po-Cheng Chiang; Chih-Chiang Huang; Wei-Jan Huang (Natural Product Research, 2012)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Assessment of the modulating effects of fructo-oligosaccharides on fecal microbiota using human flora–associated piglets - Jian Shen; Baorang Zhang; Hua Wei; Chuanyan Che; Dezhong Ding; Xiuguo Hua; Peter Bucheli; Linghua Wang; Yixue Li; Xiaoyan Pang; Liping Zhao (Archives of Microbiology, 2010)

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate - Sheng-Wei Feng; Yi-June Lo; Wei-Jen Chang; Che-Tong Lin; Sheng-Yang Lee; Yoshimitsu Abiko; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2010)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)

Eukaryotic expression and purification of anti-epilepsy peptide of Buthus martensii Karsch and its protein interactions - Zongren Wang; Wen Wang; Zhongjun Shao; Bifeng Gao; Junchang Li; Jing Ma; Jinghua Li; Honglei Che; Wei Zhang (Molecular and Cellular Biochemistry, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

Polymorphisms of GA/GT Microsatellite Loci from Anguilla japonica - Mei-Chen Tseng; Chaolun Allen Chen; Hsiao-Wei Kao; Wann-Nian Tzeng; Sin-Che Lee (Marine Biotechnology, 2001)